CIVILIZATIONAL SELF-IDENTIFICATION OF IDENTITY - YURIY, Mykhailo; KHRISTAN, Nazarii (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2023)
Abstract. The article is devoted to the socio-philosophical analysis of the problem of formation and development of civilizational self-identification of identity. The phenomenon of civilizational self-identification of identity has long attracted the attention of many researchers and is actively discussed within various social and humanitarian discourses. Three components can be distinguished in the structure of civilizational identity: mentality, locality and globality. Mentality is based on the value-semantic originality of civilization, locality is based on the ability to represent world culture in its context with one's own (ethnic, social, religious, artistic and aesthetic) means, globality indicates the contribution of local civilization to the general culture. It is the interaction of these three modes in the history of every world civilization and, in particular, the Ukrainian one, that gives rise to the dynamics of its civilizational identity. In addition, at the basis of all three modes is a value-semantic component, which is located at different levels, which can be fixed in the civilizational consciousness, which we highlight as one of the foundations of civilizational identity. The basis of civilizational identity is civilizational self-awareness, which is a set of certain spiritual values and ideas that were formed during the centuries of coexistence of nations and ethnic groups that lived in the same territory and were united by a single political system and religion.